Guidance Note On Implementing The Debt Limits Policy In Fund Supported Programs. (Policy Papers; Policy Paper ;, 2021)
The Debt Limits Policy (DLP) establishes the framework for using quantitative conditionality to address debt vulnerabilities in IMF-supported programs. In October 2020, the Executive Board approved reforms to the DLP which will enter into effect on June 30, 2021. The risk-based approach to setting debt conditionality informed by Debt Sustainability Analyses under the previous DLP approved in 2014 is maintained. The reforms aim to provide countries with more financing flexibility in practice while still adequately containing debt vulnerabilities through appropriate safeguards. This note provides operational and technical guidance related to the implementation of the DLP, including the operationalization of the approved reforms. In particular, it outlines the core principles underpinning the DLP, including when debt conditionality in IMF-supported programs is warranted and how to account for country-specific circumstances in the design of debt limits. The note also describes the process of setting and implementing debt conditionality, including: (i) identifying debt vulnerabilities to inform the focus of debt conditionality; (ii) designing debt conditionality; and (iii) implementing debt conditionality through the review cycle. The Guidance Note is intended for use by both IMF staff and country officials. In this regard, in addition to the guidance presented in the main body, the note also contains several annexes that cover definitional, technical, and operational issues arising in the determination and implementation of public debt limits.